Efficacy and safety analysis of external ventricular drainage combined with lumbar cistern drainage under intracranial pressure monitoring in severe aneurysmal subarachnoid hemorrhage. - LI, Yan-ru; ZHAO, Yong-li; HAN, Bing-sha; WANG, Ju; ZHANG, Ming; FENG, Guang (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
Objective To explore the clinical effect of external ventricular drainage combined with lumbar cistern drainage under intracranial pressure (ICP) monitoring in severe aneurysmal subarachnoid hemorrhage (SaSAH). Methods From March 2019 to March 2023, 106 patients with SaSAH admitted to Department of Neurosurgical Intensive Care Unit of He'nan Provincial People's Hospital were randomly divided into ICP monitoring group (n = 52) and without ICP monitoring group (n = 54). The ICP monitoring group was treated with external ventricular drainage combined with lumbar cistern drainage under ICP monitoring, while without ICP monitoring group was treated with external ventricular drainage combined with lumbar cistern drainage under non-ICP monitoring. Cerebrospinal fluid drainage volume, the incidence of in-hospital and long-term complications were recorded. The modified Rankin Scale (mRS) and Glasgow Outcome Scale-Extended (GOS-E) were used to evaluate the neurological prognosis, and the good prognosis rate was calculated. Results The cerebrospinal fluid drainage volume between ICP monitoring group and without ICP monitoring group was statistically significant (F = 59.843, P = 0.000), and the cerebrospinal fluid drainage volume at different measurement times was also statistically significant (F = 5.352, P = 0.000), and there was interaction between treatment factors and measurement time (F = 19.800, P = 0.000). There was no significant difference of cerebrospinal fluid drainage volume between the 2 groups on the 1-3 d (P > 0.05, for all), and the cerebrospinal fluid drainage volume of ICP monitoring group on the 4-7 d was lower than that of the without ICP monitoring group (P = 0.000, for all). In without ICP monitoring group, postoperative cerebrospinal fluid drainage volume gradually decreased, with drainage on postoperative 4-7 d being lower than on 1 d (P = 0.000, 0.000, 0.000, 0.000), 2 d (P = 0.000, 0.000, 0.000, 0.000) and 3 d (P = 0.004, 0.036, 0.000, 0.007). In ICP monitoring group, the incidence of cerebral vascular spasm (χ² = 4.850, P = 0.028), hydrocephalus (χ² = 5.804, P = 0.016), delayed cerebral infarction (χ² = 6.722, P = 0.010), brain hernia (χ² = 5.681, P = 0.017), renal failure (χ² = 5.903, P = 0.015), electrolyte disturbance (χ² = 6.389, P = 0.011) and shunt dependent hydrocephalus (χ² = 6.286, P = 0.012) were lower than without ICP monitoring group. At 6 months postoperatively, the ICP monitoring group had a lower mRS score (Z = -2.484, P = 0.013) and a higher GOS-E score (Z = -3.018, P = 0.003) than without ICP monitoring group. The good prognosis rate of ICP monitoring group was higher than that of without ICP monitoring group (χ² = 5.403, P = 0.020). Conclusions External ventricular drainage combined with lumbar cistern drainage under ICP monitoring for SaSAH can reduce the incidence of complications and improve the prognosis.